Simplified AHA/ACC ASCVD risk score implementation in a community-driven approach to initiate statin primary prevention - Adhikara, Imam Manggalya; Noviana, Uki; Thahadian, Harik Firman; Putra, Yasjudan Rastrama; Handayaningsih, Anastasia Evi; Adyarini, Dwita Dyah; Akhmadi, Akhmadi; Sujalmo, Puwardi; Widyaningsih, Andhika; Rachmawati, Annisa; Rahman, Rahma Azzalia; Meirizka, Fathina; Anggraeni, Vita Yanti (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2025)
Introduction: One of the objectives of the third Sustainable Development Goal is to lower the prevalence of non-communicable diseases (NCD). Cardiovascular disease (CVD) is one of the NCDs that remains the primary cause of mortality in Indonesia and the rest of the world. The most common CVD is coronary artery disease (CAD). It is crucial to perform risk factor assessments on individuals to facilitate early intervention and prevention. A simple instrument to stratify the population's CVD risk factor is the atherosclerotic cardiovascular disease (ASCVD) Risk Score. This study aims to determine the CAD risk stratification through screening using the ASCVD Risk Score in the Sumberadi, Mlati, Sleman, Yogyakarta populations.Methods: A descriptive study screening for CAD was conducted in a population of Sumberadi aged >15 years, especially aged 40-75 years old. The instrument used in this study was the simplified ASCVD Risk Score. The risk factors for CAD, including blood pressure, blood glucose, and cholesterol, were measured with Indonesian-standard instruments. Data was collected by Posbindu cadres with the aid of the research team. Data was analyzed univariately and presented in the form of a descriptive table.Results: This study's sample is mainly female (87%), and the age average is 48.4 ± 9.6 years old. The samples mostly have normal random blood glucose(RBG) levels (82.6%) with a mean of 117.9 ± 55.2 mg/dL. Meanwhile, the total cholesterol level of the samples is mainly normal (51.6%) with a mean of 201.4 ± 40.2 mg/dL. Four samples of people aged>75 years old needed expert consultation. The remaining 403 samples were classified based on the statin requirements (no statin required, moderate-intensity statin, and high-intensity statin). The 148 samples require moderate-intensity statin, and 64 require high-intensity statin.Conclusion: Half of the subjects in this study were included in the statin-required group. And none of them received statin as CAD primary prevention strategy. Most CAD risk factors are conditions that have no symptoms and remain neglected in the population. Therefore, screening CAD risk in the population with simple and easy instruments is still needed to detect individual CAD-risk profiling early. The screening program enables delegates to the Posbindu's cadres who the expertise had trained.